How runaway stars boost galactic outflows. Issue 3 (7th April 2020) - Andersson, Eric P; Agertz, Oscar; Renaud, Florent
ABSTRACT: Roughly 10 per cent of OB stars are kicked out of their natal clusters before ending their life as supernovae. These so-called runaway stars can travel hundreds of parsecs into the low-density interstellar medium, where momentum and energy from stellar feedback is efficiently deposited. In this work, we explore how this mechanism affects large-scale properties of the galaxy, such as outflows. To do so we use a new model that treats OB stars and their associated feedback processes on a star-by-star basis. With this model, we compare two hydrodynamical simulations of Milky Way-like galaxies, one where we include runaways, and one where we ignore them. Including runaway stars leads to twice as many supernovae explosions in regions with gas densities ranging from $10^{-5}\, \mathrm{\, cm^{-3}}$ to $10^{-3}\, \mathrm{\, cm^{-3}}$ . This results in more efficient heating of the inter-arm regions, and drives strong galactic winds with mass loading factors boosted by up to one order of magnitude. These outflows produce a more massive and extended multiphase circumgalactic medium, as well as a population of dense clouds in the halo. Conversely, since less energy and momentum is released in the dense star-forming regions, the cold phase of the interstellar medium is less disturbed by feedback effects.